Evaluation of Rapid Treponemal Test For Serodiagnosis of Syphilis - Zaheer-ud-Din; Gill, Maria Mushtaq; Mirza, Irfan Ali; Riaz, Muhammad Omair; Naqvi, Sakeenah Hussain; Imtiaz, Anam (Pakistan Armed Forces Medical Journal, 2026)
Objective: To evaluate the diagnostic accuracy of a commercial treponemal immunochromatographic test (ICT) R-test Syphilis Ab Rapid test, using positivity on two treponemal tests: Treponema pallidum haemagglutination assay (TPHA) and syphilis enzyme-linked immunosorbent assay (ELISA) as reference method for serodiagnosis of syphilis, as per European Center for Disease Prevention and Control (ECDC) algorithm. Study Design: Cross sectional validation study. Place and Duration of Study: Department of Microbiology, Armed Forces Institute of Pathology (AFIP), Rawalpindi, Pakistan, from Jul to Dec 2023. Methodology: A total of 52 samples were analyzed, where samples detected positive on both TPHA and ELISA were considered as true positives while samples testing negative by both TPHA and ELISA were considered as true negatives. Results of ICT were then compared to these. Data were incorporated in Microsoft (MS) Excel and then analyzed using Statistical Package for Social Sciences (SPSS) version 26.00. Results: Out of 55 collected samples, 52 were analyzed of which 27(52.00%) samples were positive and 24(46.00%) were negative by both the ICT method and the ELISA/TPHA combination (ECDC algorithm) while 1(2.00%) was detected positive by ECDC approach and negative by ICT method. Therefore, ICT was found to have sensitivity, specificity, accuracy and Cohen’s kappa coefficient of 96.43%, 100.00%, 98.07% and 0.96 respectively. Conclusion: The treponemal ICT (R-test Syphilis Ab Rapid test) was found to be highly sensitive, specific and accurate test for serodiagnosis of syphilis, making it a reliable and rapid diagnostic tool.